Cash flow volatility and trade credit in Asia. Issue 2 (1st March 2019) - Harris, Chris; Roark, Scott; Li, Zhe
Abstract : Purpose: The purpose of this paper is to identify the relation between cash flow volatility and trade credit offered by firms in developing Asian economies. Design/methodology/approach: The study conducts country fixed effect regressions testing the relationship between cash flow volatility and firm investment in trade credit. The relationship is then examined with all firms separated into two groups based on firm size, and then again comparing the relation before and after the 2008 finasncial crisis. Findings: Higher levels of cash flow volatility are negatively related to the amount of trade credit offered. The negative relationship with cash flow volatility is greater amongst smaller firms that may have less access to external sources of capital. Additionally, the negative relationship is greater following the 2008 financial crisis. Practical implications: Trade credit plays an important role in the business process, particularly in developing economies. However, these firms may not be able to maintain their investment in trade credit when experiencing greater levels of cash flow volatility. These results are especially pronounced after the 2008 financial crisis and for small firms. Originality/value: This study identifies an important connection between cash flow volatility and firm investment in trade credit among firms in developing Asian economies.